2020
DOI: 10.3390/cryst10030191
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Fluorine Substitution for –OH Group on the Luminescence Property of Eu3+ Doped Hydroxyapatite

Abstract: In this study, different fluoridated hydroxyapatite doped with Eu3+ ion nanoparticles were prepared by the hydrothermal method. The relationship between luminescence enhancement of Eu3+ ions and a fluorine substitution ratio for hydroxyl group in hydroxyapatite was discussed. Moreover, the effect of fluorine substitution for a hydroxyl group on phase composition, crystallinity, and crystal size was studied. Phase composition and chemical structures were identified by X-ray diffraction (XRD) and Fourier Transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…In the case of cerium-doped HAp, the luminescence quenching occurred between the nearest cerium ions in the matrix as reported by Kolesnikov et al [48]. Various fluoridated HAp doped with Eu 3+ ion nanoparticles were prepared by hydrothermal technique and the fluorine ions could influence the crystal field environment for luminescence conversion [49]. Reddy et al observed a strong green emission from Ni 2+ -doped Ca-Li HAp (CLHA) [50].…”
Section: Introductionmentioning
confidence: 82%
“…In the case of cerium-doped HAp, the luminescence quenching occurred between the nearest cerium ions in the matrix as reported by Kolesnikov et al [48]. Various fluoridated HAp doped with Eu 3+ ion nanoparticles were prepared by hydrothermal technique and the fluorine ions could influence the crystal field environment for luminescence conversion [49]. Reddy et al observed a strong green emission from Ni 2+ -doped Ca-Li HAp (CLHA) [50].…”
Section: Introductionmentioning
confidence: 82%
“…Apatite (Ap) is a large family of compounds commonly occurring in nature. Calcium hydroxyapatite (Ca 10 (PO 4 )6(OH) 2 – CaHAp) is ideal representative of this family of minerals, which can be easily doped with different kinds of ions [ 1 , 2 ]. Apatite is applied in plenty industrial fields as catalysts, laser hosts, luminescent materials, gas sensors, ionic conductors and adsorbents [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…All publications in this Special Issue are original contributions. Different materials doped with Rare Earth Elements are presented in the publications, among them nanoparticles of Zr 1-x Eu x O 2-0.5x [1], fluoridated hydroxyapatite [2], Bi 12 GeO 20 sillenite bulk crystals [3], GdSb 2 O 4 Br, TbSb 2 O 4 Br [4], and LuVO 4 [5].…”
mentioning
confidence: 99%
“…The influence of a Rare Earth Element on luminescence properties is demonstrated by Eu 3+ -doped fluoridated hydroxyapatite. The relationship between the luminescence enhancement of Eu 3+ ions and the fluorine substitution ratio for hydroxyl groups in hydroxyapatite was discussed by Zhang et al [2]. The effects of the substitution of hydroxyl groups by fluorine on the phase composition, crystallinity, and crystal size were studied.…”
mentioning
confidence: 99%
See 1 more Smart Citation